Արեւմտահայերէն եւ արեւելահայերէն բառապաշարի տարբերութիւններ`ըստ արեւմտահայերէն ուիքիփետիայի - Ստեփանեան, Ազնիւ (ԳԱԱ ԼԻ հրատ․)
In the work, we singled out 70 words, classified them according to parts of speech, and noted their semantic peculiarities. Of 70 words: a- 35 are nouns, 6 of which have the same phonetic structure, but have different meanings. b- 12 are verbs, 11 are adjectives and adverbs, and 16 are Armenian words for foreign words /foreign words in Armenian/. Bearing in mind that today, the online platform has become the source of our daily use, it is possible to research this area deeply. In the Western-speaking Diaspora communities, some words may be deprived of meaning and manifested with new meanings, influenced by Eastern Armenian and the language culture of the given country. Therefore, one should be armed and flexible with the perspective of preserving the language.
Keywords: Հայոց լեզու; Լեզվաբանություն